2023
DOI: 10.1029/2023ja032024
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Study on the Acceleration Conditions of Ultrarelativistic Electrons in the Earth's Outer Radiation Belt During Geomagnetic Storms

JingRun Chen,
ChaoLing Tang,
Xinxin Chu
et al.

Abstract: Using the data from Van Allen Probes, we statistically study the acceleration conditions of ultrarelativistic electrons (Ek > 3 MeV) in the Earth's outer radiation belt. Based on the different high energy cutoffs of ultrarelativistic electrons, the acceleration events of ultrarelativistic electrons are divided into the four groups of “3.4 MeV events,” “5.2 MeV events,” “6.3 MeV events,” and “7.7 MeV events.” According to different solar wind and substorm conditions during the recovery stage, we classify sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 63 publications
(145 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have shown that high solar wind speed (V sw > 500 km/s) and continuous substorms play an important role in the acceleration of ultrarelativistic electrons in the Earth's outer radiation belt (e.g., Baker et al, 1997;Baker et al, 2019;Hajra et al, 2015;Kim et al, 2015;Li et al, 2015;Zhao et al, 2019a). Using the data from Van Allen Probes, Chen et al (2023) statistically studied 82 acceleration events of ultrarelativistic electrons in the outer radiation belt. They found that the acceleration of ultrarelativistic electrons at different energies requires the different solar wind speeds and different substorm activities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that high solar wind speed (V sw > 500 km/s) and continuous substorms play an important role in the acceleration of ultrarelativistic electrons in the Earth's outer radiation belt (e.g., Baker et al, 1997;Baker et al, 2019;Hajra et al, 2015;Kim et al, 2015;Li et al, 2015;Zhao et al, 2019a). Using the data from Van Allen Probes, Chen et al (2023) statistically studied 82 acceleration events of ultrarelativistic electrons in the outer radiation belt. They found that the acceleration of ultrarelativistic electrons at different energies requires the different solar wind speeds and different substorm activities.…”
Section: Discussionmentioning
confidence: 99%
“…In this event, the flux of 5.2 MeV electrons did not enhance (Figure 1C). According to the definition of Chen et al (2023), this storm event was defined as an event with a cutoff energy of 3.4 MeV event (Figures 1A−F).…”
Section: The May 2013 Eventmentioning
confidence: 99%
See 3 more Smart Citations